Robust communication for location-aware mobile robots using motes - Mulanda, Brian Wise (Kansas State University, 2008)
The best mode of communication for a team of mobile robots deployed to cooperatively perform a particular task is through exchange of messages. To facilitate such exchange, a communication network is required. When successful execution of the task hinges on communication, the network needs to be robust - sufficiently reliable and secure. The absence of a fixed network infrastructure defeats the use of traditional wire-based communication strategies or an 802.11-based wireless network that would require an access point. In such a case, only an ad hoc wireless network is practical. This thesis presents a robust wireless communication solution for mobile robots using motes. Motes, sometimes referred to as smart dust, are small, low-cost, low-power computing devices equipped with wireless communication capability that uses Radio Frequency (RF). Motes have been applied widely in wireless sensing networks and are typically connected to sensors and used to gather information about their environment. Communication in a mote network is inherently unreliable due to message loss, exposed to attacks, and supports very low bandwidth. Additional mechanisms are therefore required in order to achieve robust communication. Multi-hop routing must be used to overcome short signal transmission range. The ability of a mobile robot to determine its present location can be exploited in building an appropriate routing protocol. When present, information about a mobile robot's future location can aid further the routing process. To guarantee message delivery, a transport protocol is necessary. Optimal packet sizes should be chosen for best network throughput. To protect the wireless network from attacks, an efficient security protocol can be used. This thesis describes the hardware setup, software configuration, and a network protocol for a team of mobile robots that use motes for robust wireless communication. The thesis also presents results of experiments performed.
Keywords: Network; Communication; Mote; Wireless sensor network; Security; Robot; Computer Science (0984)